1975
DOI: 10.1128/iai.11.4.815-822.1975
|View full text |Cite
|
Sign up to set email alerts
|

Partial purification and characterization of RTG-2 fish cell interferon

Abstract: Interferon produced by rainbow trout gonadal cells (RTG-2) was partially purified. The physical, chemical, and biological properties of this in vitro produced fish cell interferon were studied. Purification was achieved by ultracentrifugation, molecular sieve gel chromatography, ion exchange chromatography, and polyacrylamide gel electrophoresis. The isoelectric point of RTG-2 interferon, as determined by CM-Sephadex (C-0O) chromatography, was 7.1. Filtration through Sephadex G-150 showed that RTG-2 interferon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(8 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…We considered the possibility of the inhibitor's being interferon because some investigators have reported that the size of teleost interferon was between 40 and 94 kDa (De Sena and Rio 1975;Dorson et al 1975;Tamai et al 1993); more recent studies, however, have reported that fish interferon size is between 18 and 25 kDa (Altmann et al 2003;Robertsen et al 2003;Long et al 2004), close to the size range for SI in our studies. Both interferon ␣ and ␤ are known to be stable at 56ЊC and pH 2 (Sano and Nagakura 1982).…”
Section: Biophysical Characteristics Of the Inhibitor(s)supporting
confidence: 64%
“…We considered the possibility of the inhibitor's being interferon because some investigators have reported that the size of teleost interferon was between 40 and 94 kDa (De Sena and Rio 1975;Dorson et al 1975;Tamai et al 1993); more recent studies, however, have reported that fish interferon size is between 18 and 25 kDa (Altmann et al 2003;Robertsen et al 2003;Long et al 2004), close to the size range for SI in our studies. Both interferon ␣ and ␤ are known to be stable at 56ЊC and pH 2 (Sano and Nagakura 1982).…”
Section: Biophysical Characteristics Of the Inhibitor(s)supporting
confidence: 64%
“…In addition, the molecular weight of fish interferon is higher than that determined for reptiles and higher vertebrates and as one progresses up the phylogentic scale, a reduction in the molecular weight of interferon occurs. With regard to charge and molecular weight heterogeneity, De Sena & Rio (1975) remarked that fish may produce more than one type of interferon, dependant upon the type of inducer and type of cell stimulated. A comparison of the weights obtained by Dorson, Barde & De Kinkelin (1 975) and De Sena & Rio (1975) for rainbow trout interferon suggests that fish interferon can possibly exist as a polymeric form of the basic subunit.…”
Section: Chitinasementioning
confidence: 99%
“…It is well established that fish cells can secrete IFN molecules in response to virus infection of fibroblast or epithelial cell lines in vitro (Gravel! & Malsberger, 1965;DeSena & Rio, 1975;Okamoto et ul., 1983) or in vivo (de Kinkelin et ul., 1982). Protection by these IFNs is non-specific in that it can provide protection against an unrelated virus to that which induced it (de Kinkelin et al, 1982).…”
mentioning
confidence: 99%
“…Protection by these IFNs is non-specific in that it can provide protection against an unrelated virus to that which induced it (de Kinkelin et al, 1982). Physicochemical analysis of these fish IFNs has shown they possess a molecular weight of between 26 and 94 kDa, have isoelectric focussing points of 54-7.1, and exhibit pH and temperature stability (Dorson rt ul., 1975;DeSena & Rio, 1975). The cell source.…”
mentioning
confidence: 99%